2019
DOI: 10.5005/jp-journals-10019-1229
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microleakage of Class V Restoration with Self-etch and Selective-etch Adhesive Systems: An In Vitro Study

Abstract: Purpose:This in vitro study is to evaluate the microleakage of the universal and self-etch adhesives in selective-etch and self-etch techniques by evaluating dye penetration. Materials and methods: In this study, a total of 48 restoration and caries-free maxillar or mandibular anterior teeth were used. Standardized class V cavities (1.5 mm deep, not beveled, rounded corners) were prepared on buccal surfaces of all teeth, which were gingival edges above from the enamel-cement junction. A total of 48 teeth were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…On the contrary, a study by Yalniz et al, [21,22] indicated that no statistical significant differences had been seen between the bonding techniques (selective etch and self-etch) because in selfetch adhesives, dissolution of smear layer by the acidic quality of the reactive monomers are important for demineralizing the underlying dentin similar to selective etch adhesives [21].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a study by Yalniz et al, [21,22] indicated that no statistical significant differences had been seen between the bonding techniques (selective etch and self-etch) because in selfetch adhesives, dissolution of smear layer by the acidic quality of the reactive monomers are important for demineralizing the underlying dentin similar to selective etch adhesives [21].…”
Section: Discussionmentioning
confidence: 99%
“…Self-etch universal adhesives, when applied to dentin and enamel, do not etch enamel to the same depth as 37% phosphoric acid (pH = 0.1-0.4), which is likely responsible for the high rates of microleakage in the enamel margins of cervical restoration due to their lower acidity (high pH) [15]. Yalniz et al [16] compared the microleakage of Class V restorations with self-etch and selective-etch adhesive systems and reported that the two adhesive systems showed clinically acceptable microleakage values in two different application techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In this study the incisal enamel surface was beveled to increase the surface of enamel exposed to adhesion [26] . Selective etchant adhesive technique was used in this clinical trial because of the lower sensitivity of the technique, lower microleakage score and better clinical performance [27,28] .…”
Section: One Of the Common Findings In Daily Dentalmentioning
confidence: 99%